2019
DOI: 10.1142/s0129065718500326
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Prefrontal–Thalamic–Cerebellar Circuit in Schizophrenia and Depression: Evidence From a Possible Causal Connectivity

Abstract: Neuroimaging studies have suggested the presence of abnormalities in the prefrontal-thalamic-cerebellar circuit in schizophrenia (SCH) and depression (DEP). However, the common and distinct structural and causal connectivity abnormalities in this circuit between the two disorders are still unclear. In the current study, structural and resting-state functional magnetic resonance imaging (fMRI) data were acquired from 20 patients with SCH, 20 depressive patients and 20 healthy controls (HC). Voxel-based morphome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 65 publications
3
25
0
Order By: Relevance
“…Increased FC of the thalamus with the DMN and the sensory motor areas and decreased FC with the ECN indicate that, under acute stress, while the information related to self and essential sensory is up‐regulated, executive control signals may exert greater effort in controlling sensory input, and as a result, ECN might down‐regulate thalamus activity. The altered FC changes of the thalamus to the cortical regions especially the dlPFC imply the involvement of the thalamo‐cortical circuit during stress adaption, which is in align with findings in depression (Jiang et al, ; Kang et al, ). Further causality analyses might elucidate the FC changes among different networks.…”
Section: Resultssupporting
confidence: 85%
“…Increased FC of the thalamus with the DMN and the sensory motor areas and decreased FC with the ECN indicate that, under acute stress, while the information related to self and essential sensory is up‐regulated, executive control signals may exert greater effort in controlling sensory input, and as a result, ECN might down‐regulate thalamus activity. The altered FC changes of the thalamus to the cortical regions especially the dlPFC imply the involvement of the thalamo‐cortical circuit during stress adaption, which is in align with findings in depression (Jiang et al, ; Kang et al, ). Further causality analyses might elucidate the FC changes among different networks.…”
Section: Resultssupporting
confidence: 85%
“…A partial brain area of right MFG overlapped the medial PFC, and a study on adolescent-onset schizophrenia has also shown that ReHo values in right medial PFC increased [14]. Another study has found that concomitant structural and causal connectivity deficits in medial PFC correlate with the negative symptoms of schizophrenia [54].…”
Section: Discussionmentioning
confidence: 95%
“…Neuroimaging has been broadly used in the investigation of the human brain (Jiang et al, 2019a). In particular, restingstate functional magnetic resonance imaging (fMRI) is a very useful technique (Dong et al, 2016;Jiang et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%